(untitled) (Jurnal EurekaMatika, 2020)
This text discusses two famous classical problems in geometric construction, where the only permitted tools are a compass and an unmarked straightedge. These two problems are trisecting an angle and doubling the volume of a cube, both of which will be proven impossible to construct. The proof is conducted by translating geometric problems into algebraic problems. Subsequently, the concepts of fields and vector spaces are utilized to prove the constructibility of these geometric problems. Keywords: Doubling the volume of a cube, Trisecting an angle ABSTRAK Tulisan ini membahas dua masalah klasik yang sangat terkenal di dalam lukisan geometri dimana alat yang diperbolehkan hanya jangka dan mistar tanpa skala. Kedua masalah tersebut adalah membagi tiga buah sudut dan menggandakan volume kubus, yang akan dibuktikan bahwa keduanya mustahil dapat dilukis. Pembuktian dilakukan dengan menerjemahkan permasalahan geometri menjadi permasalahan aljabar. Kemudian, digunakan konsep lapangan dan ruang vektor untuk membuktikan keterlukisan masalah lukisan tersebut.